2013
DOI: 10.1248/bpb.b12-01095
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sampling Strategy for the Estimation of Mycophenolic Acid Area under the Concentration–Time Curve Treated in Japanese Living-Related Renal Transplant Recipients with Concomitant Extended-Release Tacrolimus

Abstract: Mycophenolate mofetil (MMF) is used for oral administration to prevent rejection in renal transplant recipients, and is rapidly converted into mycophenolic acid (MPA), the active metabolite, by hydrolysis in vivo. The area under the concentration-time curve (AUC 0-12 h ) of MPA is considered to be an effective pharmacokinetics parameter for predicting acute rejection. However, frequent blood sampling is required to calculate AUC 0-12 h , which imposes a burden on patients and providers. Therefore, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Some researches have shown that the trough level of MPA may be correlated to the patient’s outcomes in kidney transplant recipients ( Borrows et al, 2006 ; Miura et al, 2011 ). However, many studies have indicated a poor correlation between single-point concentrations and MPA-AUC 0-12 h ( Barraclough et al, 2012a ; Chaabane et al, 2013 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ; Jia et al, 2017 ). The present study also revealed the same result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researches have shown that the trough level of MPA may be correlated to the patient’s outcomes in kidney transplant recipients ( Borrows et al, 2006 ; Miura et al, 2011 ). However, many studies have indicated a poor correlation between single-point concentrations and MPA-AUC 0-12 h ( Barraclough et al, 2012a ; Chaabane et al, 2013 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ; Jia et al, 2017 ). The present study also revealed the same result.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we used the stepwise analysis obtained the equations were listed in Table 4 . In the past reports, there were also no models which include single sample concentration could accuracy predict the fAUC of MPA in renal transplant recipients ( Pawinski et al, 2002 ; Baraldo et al, 2009 ; Miura et al, 2009 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ). As a result, two time points ( C 2 and C 8 ), three time points ( C 2 , C 4 , and C 8 ) and four time points ( C 1 , C 2, C 4 , and C 8 ) models were developed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the AUC 0–4h does not reflect the total exposure (AUC 0–12h ) similarly in different phases after renal transplantation. Previous research already showed that different limited sampling strategies are needed depending on the period post‐transplantation . Moreover, when using AUC 0–4h , a very strict adherence to the sampling protocol is required .…”
Section: Discussionmentioning
confidence: 99%
“…Venous blood samples were collected at 0.5, 1.5, 4, and 9 h after the morning dose of MMF. We used a validated abbreviated sampling strategy to estimate the AUC 0-12 h of MPA and MPAG instead of a full time-concentration profile [18,19] . Briefly, blood samples before and 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, 6.0, 9.0, and 12.0 h after the MMF morning dose were obtained from 42 adult renal transplant patients who used a fixed MMF dose combined with tacrolimus for at least 2 weeks.…”
Section: Collection Of the Blood Samplesmentioning
confidence: 99%